Early outcome of orchiopexy and analysis of predictive factors: A retrospective study from 2001 to 2010 in a Norwegian regional hospital. (October 2014) - Nilsson, Rasmus; Omland, Harald; Dahl, Alv A.; Johansen, Truls E. Bjerklund
Abstract Objective. The primary aim of this study was to retrospectively analyse surgical treatment for undescended testes at the Department of Urology, Telemark Hospital, Norway, and to examine whether international standards were met regarding age at surgery and outcome. The secondary aim was to identify factors that predicted an unsuccessful outcome. Material and methods. The department's medical records from 2001 to 2010 were searched, and selected variables were registered and analysed. Results. Of 205 primary orchiopexies, 81% were considered immediately successful and 94% were successful after reoperation. Median age at the time of primary surgery was 3.7 years (range 0.1–17.5 years). Fourteen per cent were operated on before the age of 2 years and 40% before the age of 3 years. There was a tendency towards lower age at surgery in the later part of the study period. Younger patients had an increased risk of a primary unsuccessful result. Procedures performed by a surgeon with a low number of operations were less often successful. Preoperative testicular location and different surgical technique did not affect outcome significantly. Conclusions. The results may seem inferior to those reported by others but comparison is uncertain owing to differences in study design, patient selection criteria and follow-up time. Although age at surgery in this series was higher than recommended, and outcome of the very youngest needs to be improved, the authors argue that the quality of treatment was acceptable. Orchiopexies should be carried out by a limited number of dedicated surgeons in each department.